Development Economics: theory and practice - Janvry, Alain De; Sadoulet, Elisabeth (New York Routledge, 2021)
Development Economics: theory and practice provides students and practioners with the perspectives and the tools they need to think analytically and critically about the current major economic development issues in the world. Alain de Janvry and Elisabeth Sadoulet identify seven key dimensions of development: growth, poverty, vulnerability, inequality, basic needs, sustainability, and quality of life, and use them to structure the contents of the text. This book gives a historical perspective on the evolution of thought in development. It uses theory and empirical analysis to present readers with a full picture of how development works, how its successes and failures can be assessed, and how alternatives can be introduced.
Keywords: Social policy; Economic policy; Development economics